Difference between Internal and External Hydration of Hardened Cement Paste under Microwave Curing. (31st October 2021) - Yan, Guoshun; Li, Jiazheng; Lin, Yuqiang; Chen, Xia
Abstract : In order to investigate the difference between internal and external hydration of hardened cement paste under microwave curing, a comparative study on the hydration products, hydration degree, fracture morphology, and pore structure between the inner part and outer part of hardened cement paste (Φ120 mm × 120 mm) under microwave curing was carried out by XRD-Rietveld refinement, TG-DSC, SEM, and MIP methods. The results show that the total hydration degree of the inner part is lower at early ages, but with the hydration, there is little difference in the hydration degree between inner and outer parts at later ages. Apart from granular AFt crystal formed in the inner part of hardened cement paste, there is little difference in the fracture morphology between internal and external hydration. The total porosity of the outer part is lower than that of the inner part.